ANALISIS TINGKAT KEPUASAN PENGUNJUNG WISATA ALAM DANAU GUNUNG TUJUH KABUPATEN KERINCI - Rahmat Al Amin; Ahyauddin Ahyauddin; Rahmad Nurmansah (Sylva Jurnal Ilmu-ilmu Kehutanan, 2026)
Gunung Tujuh Lake is one of the leading natural tourism destinations in Kerinci Regency, offering natural attractions, accessibility, amenities, and supporting services that influence visitor satisfaction. This research analyzes the differences between importance and performance levels in the factors of attraction, accessibility, amenity, and ancillary, and measures overall visitor satisfaction. A quantitative approach was applied using accidental sampling of 100 respondents. Data were analyzed using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that the average performance score was 4.00, higher than the average importance score of 3.79, with a conformity level of 106%. The CSI value of 80.35% indicates that visitors were in the very satisfied category. However, several attributes still require attention, particularly environmental cleanliness and the availability of public toilets, which showed negative gap values. Overall, the management of Danau Gunung Tujuh tourism has been able to meet and even exceed visitor expectations.